Informed consent and community engagement in open field research: lessons for gene drive science - Singh, Jerome Amir (BMC Med Ethics, 2019)
BACKGROUND: The development of the CRISPR/Cas9 gene editing system has generated new possibilities for the use of gene drive constructs to reduce or suppress mosquito populations to levels that do not support disease transmission. Despite this prospect, social resistance to genetically modified organisms remains high. Gene drive open field research thus raises important questions regarding what is owed to those who may not consent to such research, or those could be affected by the proposed research, but whose consent is not solicited. The precise circumstances under which informed consent must be obtained, and from whom, requires careful consideration. Furthermore, appropriate engagement processes should be central to any introduction of genetically modified mosquitos in proposed target settings. DISCUSSION: In this work, international guidance documents on informed consent and engagement are reviewed and applied to the genetically modified mosquito research context. Five analogous research endeavours that involve area-wide / open field experiments are reviewed. The approach of each in respect to the solicitation of individual informed consent and community engagement are highlighted. CONCLUSIONS: While the solicitation of individual informed consent in host settings of gene drive field trials may not be possible or feasible in some instances, local community and stakeholder engagement will be key to building trust towards the proposed conduct of such research. In this regard, the approaches taken by investigators and sponsors of political science field research and weather modification field research should be avoided. Rather, proponents of gene drive field research should look to the Eliminate Dengue field trials, cluster randomised trials, and pragmatic clinical trials for guidance regarding how the solicitation of individual informed consent of host communities ought to be managed, and how these communities ought to be engaged.